Un cinéma affranchi du contrôle de l’État - Nicolas Appelt (Revue des Mondes Musulmans et de la Méditerranée)
The Syrian conflict is reflected, among others, in a flood of images: in the propaganda of the regime, in the Organization of the Islamic State (OEI), in testimonies of activists or reporters. Parallel to those videos broadcasted on television or posted on social media, a Syrian cinematic creation persists outside the official production channels of the regime and despite difficulties. This cinematic creation brings a singular insight, in contrast to the image usually conveyed on Syria ; and this in various and diverse formats. Beyond the simple testimony and independently of their career path, Syrian director filmmakers give their perspective in the comprehension of the changing situation in the country, engaged, at the same time, in a reflection on cinema. The diversity of approaches shapes a fragmented, national narrative.